2-[3,5-Bis(5-bromothien-2-yl)-4H-1,2,6-thiadiazin-4-ylidene]-malononitrile - Andreas S. Kalogirou; Andreas Kourtellaris; Panayiotis A. Koutentis (Molbank)
Bromination of 2-[3,5-di(thien-2-yl)-4H-1,2,6-thiadiazin-4-ylidene]-malononitrile with N-bromosuccinimide in THF, at ca. 20 °C for 24 h gave 2-[3,5-bis(5-bromothien-2-yl)-4H-1,2,6-thiadiazin-4-ylidene]-malononitrile in 82% yield. The latter is intended as a scaffold for preparing donors for organic photovoltaics.